COMÉRCIO DE PEIXES UTILIZADOS COMO ISCA-VIVA - ROMERO, João Pedro Alves; ACUNHA, Rubia Mara Gomes; SILVA, Maria Eduarda Vasconcelos Mendes; ALMEIDA, Rômullo Guilherme; COSTA, Deliane Cristina; CAMPOS, Cristiane Meldau de (ANAIS DO ENIC, 2023)
-